Aspectos produtivos e viabilidade econômico-financeira da irrigação em sorgo forrageiro - Kirchner, Jardel Henrique (2019)
The availability of pasture during the whole year is essential for the development of the beef cattle. In the spring-summer period the pasture quality falls due to irregularity of rains. An alternative is the use of cultivated pastures, where forage sorghum has been characterized in the livestock scenario of Rio Grande do Sul due to its adaptation to this time of year and the mass production. However, to reach this potential it’s essential to guarantee the water needs, and irrigation is the alternative to increase the expected profit and maintain animal feed. However, with the increase of irrigation in the production system there is an increase in costs, which should be lower than the revenues to ensure sustainability. The objective of this study was to investigate the technical and financial feasibility for fixed conventional sprinkler irrigation in the forage sorghum for the central region of Rio Grande do Sul state. The study was conducted in the city of Santa Maria, RS, in the 2015/2016 and 2016/2017, with sowing in November of both agricultural years. The experimental design was organized in randomized blocks with four replicates and six additional irrigation levels: 0, 25, 50, 75, 100 and 125% of the reference evapotranspiration (ETo). The ETo was determined by the Penman-Monteith method (ALLEN et al., 1998).A conventional sprinkler irrigation system with a main line and six lateral lines in PVC was used and the irrigation levels were differentiated by the system operating time according to the application blade calibrated by the Christiansen Uniformity Coefficient test. In order to determine the economic and financial viability of irrigation, the determination of the maximum technical efficiency of the water use, the determination of the revenues, costs and feasibility indicators were performed, being the Net Present Value (NPV), the Internal Rate of Return ( IRR) and the Benefit / Cost Ratio. It was adopted as criterion for estimating the weight gain of the pasture supply of 4% of the live weight of the animal, the animal weight was set at 300 kg, and scenarios of average daily gains of 0.5, 1.0 and 1 were simulated, 5 kg animal-1 day-1 for the conversion of dry mass production into beef gain. The value of the kilogram of live-weight meat paid to the producer for the determination of gross income was 6 reais kg. For the determination of production costs, they were divided into fixed and variable, related and not related to irrigation. Statistically significant differences were found for productivity between the different treatments and also, between the agricultural years, as well as for the water use efficiency. In addition, it has been found that irrigation is feasible financially for most scenarios evaluated and that costs depend on the precipitation regime. It was also found economic viability of irrigation in all the indicators evaluated and variations in profitability according to the different scenarios of daily animal weight gain.